A Chronic Toxicity Study of Oral Administration of Collagen-?® Supplement using Pregnant Rabbits - Alia M. Kudayer1, Nawras A. Alwan2 , Alaa A. Sawad1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Since collagen derived products are highly used in food supplements due to its bioactive properties by influencing cellular and tissue health, flexibility with high effect of repairing and adaptation. It is necessary to carry out safety requirement of an oral chronic toxicity assessment. This study investigated the adverse effect of long term oral administration of collagen-® in pregnant rabbits. We have conducted a thirty days randomized controlled trial in pregnant rabbits. Rabbits were randomized into two groups; Group 1 (control group) were administrated with 1 ml of normal saline PO, SID while Group 2 (collagen-? group) were administered with 1 ml of collagen-?® PO, SID for one month. Bodyweight gain, viscera weight and histopathological evaluation of the individual rabbit were recorded. The results revealed that the body weight gain and visceral tissues weight in the collagen-? group were significantly lower than the control group. Moreover, various histopathological changes were recorded in heart, lungs, liver and kidneys of the collagen-? group when compared with the non-significant changes that noticed in the control group. Under the conditions of the current study, a high risk of chronic toxic effect was observed in pregnant rabbits inoculated with 1 ml of oral dose of collagen alpha supplement. This result suggests that the adverse effect of collagen derived supplements is overbalancing the benefits.